Risk and protective factors for mental health in children: the family context - Matsukura, Thelma Simões; Fernandes, Amanda Dourado Souza Akahosi; Cid, Maria Fernanda Barboza (Revista de Terapia Ocupacional da Universidade de São Paulo, 2012)
Some family characteristics can bring risks for the healthy development of children,among them stand out, low income, low parental education, high levels of family stress. Togetherwith risk factors that are subject to the children, there are the protective factors that can induce humandevelopment in the presence of risk. The aim of this study was to identify associations between childmental health and variables considered of risk or protection present in the familiar context of elementaryschool children. The research was developed with the sample of 39 guardians of children from 1st to 5thyear of elementary school, in a public school located on the outskirts of São Carlos-SP. The instrumentsused were: Strengths and Difficulties questionnaire (SDQ), Critério de Classificação EconômicaBrasil (CCEB) and the Questionário de atividades cotidianas (QAC). The statistical analysis wasdescriptive, correlational and with the comparison between the groups, using nonparametric Mann-Whitney and Kendall’s. The outcomes showed that the variable to “scolding for no reason” and“guardian plays with the child” is related with the presence of mental health problems. In contrast, thevariable “rules and responsibilities in the family” was related to higher levels of child mental health.